2010
DOI: 10.1016/j.neuroimage.2010.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Causal Modelling and physiological confounds: A functional MRI study of vagus nerve stimulation

Abstract: Dynamic Causal Modelling (DCM) has been proposed to estimate neuronal connectivity from functional magnetic resonance imaging (fMRI) using a biophysical model that links synaptic activity to hemodynamic processes. However, it is well known that fMRI is sensitive not only to neuronal activity, but also to many other psychophysiological responses which may be task-related, such as changes in cardio-respiratory activity. They are not explicitly taken into account in the generative models of DCM and their effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 56 publications
6
39
0
1
Order By: Relevance
“…The second one involves areas that are essential to integrate gastro-duodenal mechanosensory information (hippocampus, pallidum) so to give a hedonic value to these. Similar results have been reported in rats either using PET (Dedeurwaerdere et al, 2005) or MRI (Reyt et al, 2010). Unlike behavioral effects that take several weeks to be identified, alterations in brain metabolism identified by PET imaging were present 1 week only after the onset of VNS therapy.…”
Section: Invasive Neuromodulation Strategies: Recent Developments Andsupporting
confidence: 88%
“…The second one involves areas that are essential to integrate gastro-duodenal mechanosensory information (hippocampus, pallidum) so to give a hedonic value to these. Similar results have been reported in rats either using PET (Dedeurwaerdere et al, 2005) or MRI (Reyt et al, 2010). Unlike behavioral effects that take several weeks to be identified, alterations in brain metabolism identified by PET imaging were present 1 week only after the onset of VNS therapy.…”
Section: Invasive Neuromodulation Strategies: Recent Developments Andsupporting
confidence: 88%
“…The technique enables multiple circuit abnormalities to be probed either as a data-driven or as an a-priori approach prior to dissecting more localized dysfunction with causal-based fMRI methods (David et al, 2008; Reyt et al, 2010; Rehme et al, 2011). Since the first rsfMRI publication showing the utility of resting state fMRI (Biswal et al, 1995), there has been a great deal of work that illustrates its sensitivity to altered brain function in a large number of disease states, indicating its potential as a clinical tool for diagnosing and monitoring dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, even low frequency VNS (1 Hz) discretely affected the level of c-fos expression in the rat NTS, compared to shamoperated animals (Osharina et al, 2006). Regarding the frequency of stimulation, if low frequency (5-10 Hz) is supposed to activate vagal efferents (Bonaz et al, 2013), we have reported in rats that even low frequency stimulation at 5 Hz was able to induce modifications of activation in the NTS, the first target of the VN in the brain, as well as in numerous areas of its brain projections (Reyt et al, 2010). Brain imaging studies in human as well as c-fos activation in the NTS and other NTS brain related nuclei have been reported in humans and animals under VNS respectively (Lomarev et al, 2002;Osharina et al, 2006).…”
Section: Questions-future For Vagus Nerve Stimulation In Inflammatorymentioning
confidence: 97%